General plant safety in a textile factory - Samsuri, Ariffin; Balasundram, Suresh (1999)
The paper describes a research work to solve the safety problem in a textile factory. Accident cases were identified in all departments, which were spinning, dyeing and knitting departments, and general cases within the factory. From the analysis, it was observed that for the past 5 years, 31-42% of the accidents came from the spinning department with the highest is spinning accidents. Spinning accidents came from two particulars machinces; spinning section and roving machines. The general cause of the accidents was due to carelessness, improper training, and improper attire during work. Based on the finding, suggestions were made, especially for the spinning department workers. Among them were some basic training and also proper attire during work. These suggestions at least to prevent repetitive accidents from occuring.